2013
DOI: 10.1558/cam.v9i3.203
|View full text |Cite
|
Sign up to set email alerts
|

Preserving the child as a respondent: Initiating patient-centered interviews in a US outpatient tertiary care pediatric pain clinic

Abstract: This article identifies some of the challenges of implementing patient-centeredness in multiparty clinical visits. Specifically, it describes four interview practices with which clinicians address these challenges in a US outpatient tertiary care pediatric pain clinic. Using the qualitative method of conversation analysis, we analyze clinicians' child-directed (ages 10-18) interviewing during the initial stage of 51 intake visits. In particular, we analyze the challenges involved in open-ended questioning, a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…21 Having flexible and innovative communication skills with both child and parents can improve rapport and promote patient/familycenteredness care. 22 As the nurses revealed, it takes time to build rapport and trust with a child and their family but it has shown to improve outcome and satisfaction. 21 A child dying is unnatural and nurses in our study found dealing with emotions arising within themselves and from parents challenging.…”
Section: Discussionmentioning
confidence: 99%
“…21 Having flexible and innovative communication skills with both child and parents can improve rapport and promote patient/familycenteredness care. 22 As the nurses revealed, it takes time to build rapport and trust with a child and their family but it has shown to improve outcome and satisfaction. 21 A child dying is unnatural and nurses in our study found dealing with emotions arising within themselves and from parents challenging.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, because a response was not an interactional necessity for the conversation to proceed, the tag questions did not place a burden of responding on the child in a way that a more open, information-soliciting question might do. The use of tag questions in this environment builds on prior research by Clemente (2009) and Clemente et al (2012), who showed that practices such as closed-ended questioning place fewer demands on the child, which may help to reduce the risk of no response, or a parent responding instead of the child.…”
Section: Discussionmentioning
confidence: 98%
“…Children's talk, however, typically only accounts for around 5% of the conversation during paediatric consultations, with most talk being a dyadic exchange between a health-care professional and the child's parent or guardian (Cahill, 2010;Cahill & Papageorgiou, 2007). Clinicians and parents or guardians face the challenge of providing opportunities for children to participate but without imposing burdens on the child that may make them unwilling or unable to actively participate in the consultation (Clemente et al, 2008(Clemente et al, , 2012.…”
Section: Child Agency In Paediatric Health Care Appointmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decision‐making highlights how the child participates and is listened to together with professionals and parents. However, situating the child at the centre of the conversation at the start of the consultation can be challenging (Clemente and others, ). Studies have found that professionals rarely discuss children's involvement as a topic of importance (Garth and others, ; Schalkers and others, ).…”
Section: Introductionmentioning
confidence: 99%